Activation of Human Auditory Cortex in Retrieval Experiments: An fMRI Study. Issue 3 (1998) - Gaschler-Markefski, Birgit; Baumgart, Frank; Tempelmann, Claus; Woldorff, Marty G.; Scheich, Henning
Abstract : In a previous functional magnetic resonance (fMRI) study, a subdivision of the human auditory cortex into four distinct territories was achieved. One territory (T1a) exhibited functional specialization in terms of a foreground-background decomposition task involving matching-to-sample monitoring on tone sequences. The present study more specifically determined whether memory-guided analysis of tone sequences is part of the T1a specialization. During the encoding periods, an arbitrary and unfamiliar four-tone-sequence (melody) played by one instrument was presented. The melody-instrument-combination was different in each period. During subsequent retrieval periods, learned and additional combinations were presented, and the tasks were either to detect the target melodies (experiment I) or the target instruments (experiment II). T1a showed larger activation during the melody retrieval. The results generally suggest that (1) activation of T1a during retrieval is determined less by the sound material than by the executed task, and (2) more specifically, that memory-guided sequential analysis in T1a is dominant over recognition of characteristic complex sounds.